2013
DOI: 10.1155/2013/790323
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Size of Gold Nanoparticles for Surface‐Enhanced Raman Spectroscopy under Different Conditions

Abstract: Gold nanoparticles have been used as effective surface-enhanced Raman spectroscopy (SERS) substrates for decades. However, the origin of the enhancement and the effect of the size of nanoparticles still need clarification. Here, gold nanoparticles with different sizes from 17 to 80 nm were synthesized and characterized, and their SERS enhancement toward both 4-aminothiophenol and 4-nitrothiophenol was examined. For the same number of nanoparticles, the enhancement factor generated from the gold nanoparticles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
108
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(125 citation statements)
references
References 31 publications
16
108
0
1
Order By: Relevance
“…[74][75][76]84 These higher order modes decrease the collective motion of electrons leading to wider plasmon band widths 72,77,85,86 and lower EM enhancements. 78,80,81 As particles decrease in size, on the other hand, less area is available to collect the incident light (smaller cross sections). Typically, the highest enhancements for silver and gold nanoparticles with spherical shapes are observed in the size range of 40−60 nm diameter.…”
Section: Electromagnetic Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…[74][75][76]84 These higher order modes decrease the collective motion of electrons leading to wider plasmon band widths 72,77,85,86 and lower EM enhancements. 78,80,81 As particles decrease in size, on the other hand, less area is available to collect the incident light (smaller cross sections). Typically, the highest enhancements for silver and gold nanoparticles with spherical shapes are observed in the size range of 40−60 nm diameter.…”
Section: Electromagnetic Enhancementmentioning
confidence: 99%
“…Typically, the highest enhancements for silver and gold nanoparticles with spherical shapes are observed in the size range of 40−60 nm diameter. 80,81,87 Equation 1 would suggest that the optimal condition for maximal SERS intensities is when the LSPR peak has high overlap with the laser line and Raman-scattered frequencies. However, experimental observations have shown that this is not always the case.…”
Section: Electromagnetic Enhancementmentioning
confidence: 99%
“…This means that the samples with small size of AuNS and low LSPR peaks are not able to assist urea molecules to produce the Raman scattering signal because smaller nanoparticles will have less surface area and low conductivity of electron for oscillation. Thus, less light is absorbed by the surface which weakens its electromagnetic field and reduces the signal of Raman scattering [7]. From these results, we may concluded that the effective sizes of the AuNS to enhance the Raman scattering are about 15-20 nm.…”
Section: Methodsmentioning
confidence: 82%
“…Figure 1E shows that the absorption spectra of GA-AuNPs had an absorption maximum at 540 nm. Similarly, the spectra of AuNPs with the mean size of 60 nm showed maximal absorption at 540 nm (Hong and Li, 2013).…”
Section: Other Testsmentioning
confidence: 91%